Scaling out sweetpotato and potato-led interventions to improve nutrition and food security in Tigray and SNNPR, Ethiopia - International Potato Center (2016)
Strengthening the seed value chain is key to any sweetpotato intervention. Getting disease-free starter material is essential. Quality orange-fleshed sweetpotato vines (16.9 million cuttings) have been distributed reaching 36,460 households in two and a half years.